Perlindungan Hukum Konsumen Atas Kepemilikan Sertifikat dalam Pembiayaan Pemilikan Rumah di BJB Syariah - Sekarrini, Ayu; Anggraini, A.M Tri; Setyowati, Retno Kus (Universitas Pahlawan Tuanku Tambusai, 2025)
As one of the sectors of the financial services industry, banks play an important role in ensuring that people's home ownership rights are fulfilled. One type of credit provided by banking institutions is home ownership loans and in Islamic banking is known as home ownership financing. The purpose of this study is to analyze about: (1) Consumer legal protection of certificate ownership whose settlement process is not in line with the period agreed by the parties in BJB Syariah. (2) Legal remedies of consumers who are harmed due to the process of completing the certificate that is not in line with the time period agreed by the parties in BJB Syariah. This study uses normative research that focuses on legal protection for consumers in financing home ownership in banks. The approach uses a legal approach and a conceptual approach. The data analysis used is qualitative analysis. The results of the study show that the form of legal protection provided to consumers has been regulated in the UUPK, namely developers and notaries are sanctioned for violating consumer rights in terms of certificate ownership. Consumer legal remedies can be resolved through 2 dispute resolution channels, namely the court/litigation route and the out-of-court/non-litigation route. The mechanism for resolving disputes outside the court includes peaceful settlement, settlement through BPSK, and complaint services through LAPS SJK. The legal choice agreed upon by consumers, developers and banks is reconciliation between the parties.